Causal relationships between COVID-19 and osteoporosis: a two-sample Mendelian randomization study in European population - Zhang, Kai; Shi, Wei; Zhang, Xinglong; Pang, Ran; Liang, Xinyu; Xu, Qian; Xu, Chunlei; Wan, Xin; Cui, Wenhao; Li, Dong; Jiang, Zhaohui; Liu, Zhengxuan; et al. (Frontiers in Public Health, 2023)
Introduction The causal relationship between Coronavirus disease 2019 (COVID-19) and osteoporosis (OP) remains uncertain. We aimed to assess the effect of COVID-19 severity (severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, COVID-19 hospitalization, and severe COVID-19) on OP by a two-sample Mendelian randomization (MR) study. Methods We conducted a two-sample MR analysis using publicly available genome-wide association study (GWAS) data. Inverse variance weighting (IVW) was used as the main analysis method. Four complementary methods were used for our MR analysis, which included the MR‒Egger regression method, the weighted median method, the simple mode method, and the weighted mode method. We utilized the MR-Egger intercept test and MR pleiotropy residual sum and outlier (MR-PRESSO) global test to identify the presence of horizontal pleiotropy. Cochran's Q statistics were employed to assess the existence of instrument heterogeneity. We conducted a sensitivity analysis using the leave-one-out method. Results The primary results of IVW showed that COVID-19 severity was not statistically related to OP (SARS-CoV-2 infection: OR (95% CI) = 0.998 (0.995～1.001), P = 0.201403; COVID-19 hospitalization: OR (95% CI) =1.001 (0.999～1.003), P = 0.504735; severe COVID-19: OR (95% CI) = 1.000 (0.998～1.001), P = 0.965383). In addition, the MR-Egger regression, weighted median, simple mode and weighted mode methods showed consistent results. The results were robust under all sensitivity analyses. Conclusion The results of the MR analysis provide preliminary evidence that a genetic causal link between the severity of COVID-19 and OP may be absent.